2004
DOI: 10.1111/j.1523-1755.2004.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of glomerular hemodynamic changes in diabetic rats: Effects of insulin ARB

Abstract: This imaging procedure allowed us to evaluate glomerular microcirculation in vivo, including the diameters of AA and EA, erythrocyte velocity, and volume flow. DM significantly induced glomerular hemodynamic alteration and renal hypertrophy. DM treated with either insulin or ARB ameliorated these changes. This study shows that progress in imaging technology promises to make major contributions to revealing the involvement of hemodynamic changes in glomerular diseases, aiding prognosis and the monitoring of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 44 publications
(40 reference statements)
1
36
0
Order By: Relevance
“…Glomerular hyperfiltration, altered glomerular hemodynamics (increased ratio of afferent to efferent arteriole diameter), glomerular hypertrophy, and increased glomerular permeability to macromolecules have been confirmed (24,48). The beneficial effects of RAS blockade were also demonstrated (24,48). Other morphological and functional changes in the glomerulus (for example, in glomerulosclerosis) can be visualized using MPM (see below).…”
Section: Imaging Renal Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerular hyperfiltration, altered glomerular hemodynamics (increased ratio of afferent to efferent arteriole diameter), glomerular hypertrophy, and increased glomerular permeability to macromolecules have been confirmed (24,48). The beneficial effects of RAS blockade were also demonstrated (24,48). Other morphological and functional changes in the glomerulus (for example, in glomerulosclerosis) can be visualized using MPM (see below).…”
Section: Imaging Renal Pathologymentioning
confidence: 99%
“…Functional changes in the early phase of diabetes have been visualized in the rat kidney using MPM (48) or conventional confocal fluorescence microscopy (24). Glomerular hyperfiltration, altered glomerular hemodynamics (increased ratio of afferent to efferent arteriole diameter), glomerular hypertrophy, and increased glomerular permeability to macromolecules have been confirmed (24,48).…”
Section: Imaging Renal Pathologymentioning
confidence: 99%
“…In rats with two-kidney, one figure-eight wrap (Grollman) hypertension, renal interstitial fluid bradykinin, NO x , and cyclic GMP were higher in the contralateral kidney than in the wrapped kidney; losartan normalized systolic blood pressure and increased renal function, interstitial fluid bradykinin, NO x , and cyclic GMP only in the contralateral kidneys, whereas PD123319 increased blood pressure and decreased these interstitial fluid substances in both kidneys, suggesting that ANG II mediates renal production of bradykinin, which in turn, releases NO and cyclic GMP via stimulation of AT 2 receptors . Li et al (2004) found that rats with diabetes mellitus exhibited glomerular hemodynamic alteration and renal hypertrophy, and treatment with either insulin or candesartan ameliorated these changes, possibly by a suppression of enhanced renal expression of eNOS in diabetic rats.…”
Section: Other Vasculaturesmentioning
confidence: 99%
“…37 Briefly, photographs of 50 glomeruli were taken using a digital camera at the time of sieving, and the surface areas were traced using a computer-assisted color image analyzer Image-Pro (version 2.0; Media Cybernetics, Silver Spring, MD). V G was calculated using the equation V G ϭ 4/3(area/) 3/2 .…”
Section: Morphometric Measurement Of Glomerular Volumementioning
confidence: 99%